2013
DOI: 10.1021/jp409777p
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and Seeding of Amylin Fibril-Like Oligomers

Abstract: Seeding a protein solution with pre-formed fibrils can enhance dramatically the growth rate of amyloids. As the seeds do not need to be of the same protein, seeding may account for the observed correlations between amyloid diseases. In an effort to understand better the molecular mechanisms behind cross seeding we have studied in silico the effect of mutations on the seeding of amylin fibrils. Our investigations of the structural stability of decamers of wild type amylin peptides, of Y37L mutants, and of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 64 publications
(141 reference statements)
5
35
0
Order By: Relevance
“…In the Y37L mutants, the lack of tyrosine-specific interactions causes significant larger flexibility of the C terminal region than in the wild-type fibril. This hinders elongation of the Y37L mutant fibril leading to the longer lag times during aggregation that are observed in experiments for this mutant (Bernhardt, Berhanu, & Hansmann, 2013).…”
Section: Amyloid Aggregation and Cross Seedingmentioning
confidence: 88%
“…In the Y37L mutants, the lack of tyrosine-specific interactions causes significant larger flexibility of the C terminal region than in the wild-type fibril. This hinders elongation of the Y37L mutant fibril leading to the longer lag times during aggregation that are observed in experiments for this mutant (Bernhardt, Berhanu, & Hansmann, 2013).…”
Section: Amyloid Aggregation and Cross Seedingmentioning
confidence: 88%
“…This could be either a consequence of the low solubility or the tight cross-β-structure of the amyloid fibrils [56]. Furthermore, the presence of amyloid fibrils is known to have a strong promoting effect on the aggregation process [5758], whereby nucleation, together with the unfavorable structure could conceal the effect of phosphorylation. Thus, a further proof was the chemically phosphorylated peptide P C KFM6 which completely lost its ability to undergo a conformational transition and remains random coil even at higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results reported that six polymorphic structures were categorized depending on the interfacing β‐strands, that is, whether the strands included the N‐terminal or C‐terminal residue, or were in the β‐strand direction along to fibril axis. Therefore, we constructed six polymorphic Aβ pair structures per each model and length type according to previous studies . The six structures were CCnn, CCun, NNnn, NNun, NCnn, and NCun (Fig.…”
Section: Methodsmentioning
confidence: 99%